Experiential - Participatory Teaching Techniques in Primary Education: Exploring the Views of Greek Teachers - Evangelou, Filippos (Journal of Education and Training, 2023)
This research seeks to explore the views of Greek teachers in primary schools on the use of experiential - participatory teaching techniques in the classroom. More specifically, it seeks to investigate whether the use of experiential - participatory techniques will: improve the quality of teaching; make appropriate use of modern learning principles in the context of the functioning of the educational group; and make appropriate use of the specific characteristics, educational needs and interests of students. The research sample consisted of two hundred and ten Greek teachers. A structured questionnaire was used to conduct the research and collect data. The main findings of this research are coded as follows: (a) A very high percentage of teachers state that the quality of teaching is improved by using experiential - participatory teaching techniques, (b) A very high percentage of teachers state that by using experiential - participatory teaching techniques, modern learning principles are appropriately utilized in the context of the educational team functioning, (c) A fairly high percentage of teachers state that the use of experiential - participatory teaching techniques exploits the specific characteristics, educational needs and interests of students.